Possible Contrast Media Reduction with Low keV Monoenergetic Images in the Detection of Focal Liver Lesions: A Dual-Energy CT Animal Study - Chung, Yong Eun (PLoS One, 2015)
OBJECTIVE: To investigate the feasibility of dual-energy CT for contrast media (CM) reduction in the diagnosis of hypervascular and hypovascular focal liver lesions (FLL). SUBJECTS AND METHODS: The Institutional Animal Care and Use Committee approved this study. VX2 tumors were implanted in two different segments of the liver in 13 rabbits. After 2 weeks, two phase contrast enhanced CT scans including the arterial phase (AP) and portal-venous phase (PVP) were performed three times with 24-hour intervals with three different concentrations of iodine, 300 (I(300)), 150 (I(150)) and 75 mg I/mL (I(75)). The mean HU and standard deviation (SD) were measured in the liver, the hypervascular portion of the VX2 tumor which represented hypervascular tumors, and the central necrotic area of the VX2 tumor which represented hypovascular tumors in 140kVp images with I(300) as a reference standard and in monoenergetic images (between 40keV and 140keV) with I(150) and I(75). The contrast-to-noise ratio (CNR) for FLLs and the ratio of the CNRs (CNR(ratio)) between monoenergetic image sets with I(150) and I(75), and the reference standard were calculated. RESULTS: For hypervascular lesions, the CNR(ratio) was not statistically different from 1.0 between 40keV and 70keV images with I(150), whereas the CNR(ratio) was significantly lower than 1.0 in all keV images with I(75). For hypovascular lesions, the CNR(ratio) was similar to or higher than 1.0 between 40keV and 80keV with I(150) and between 40keV and 70keV with I(75). CONCLUSIONS: With dual-energy CT, the total amount of CM might be halved in the diagnosis of hypervascular FLLs and reduced to one-fourth in the diagnosis of hypovascular FLLs, while still preserving CNRs.